2020
DOI: 10.1111/jan.14731
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and short‐term outcomes of post‐stroke fatigue in initial phase of transition from hospital to home: A prospective observational study

Abstract: Aim To analyse the interactions of associated factors with post stroke fatigue (PSF) after discharge home and determine the predictors of PSF and their impact on stroke survivors. Design A prospective observational study. Methods A total of 94 patients with acute stroke were recruited between May 2019 ‐July 2020. The main outcomes were fatigue, depression, insomnia, sarcopenia, and health‐related quality of life (HRQOL) and were assessed at admission and 1 month after discharge. Fatigue was measured using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Notably, when fatigue and sleep difficulties were entered into the logistic regression together, it was fatigue that was the contributing factor accounting for increased odds of PSD. Fatigue and sleep difficulties are highly correlated, and both can contribute to poststroke depression such that sleep deprivation worsens mood when the body cannot refresh, and when the body feels tired, the mind can have less reserve to fight ruminations and worries [ 27 ] further contributing to depression. Importantly, the American Heart Association Council on Cardiovascular and Stroke Nursing and Stroke Council made it a point of emphasis to find effective interventions for fatigue that can be disabling and can limit recovery after stroke [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, when fatigue and sleep difficulties were entered into the logistic regression together, it was fatigue that was the contributing factor accounting for increased odds of PSD. Fatigue and sleep difficulties are highly correlated, and both can contribute to poststroke depression such that sleep deprivation worsens mood when the body cannot refresh, and when the body feels tired, the mind can have less reserve to fight ruminations and worries [ 27 ] further contributing to depression. Importantly, the American Heart Association Council on Cardiovascular and Stroke Nursing and Stroke Council made it a point of emphasis to find effective interventions for fatigue that can be disabling and can limit recovery after stroke [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Fatigue Assessment Scale is a short 10-item self-report scale evaluating symptoms of chronic fatigue, with a high internal consistency of 0.90 ( 33 ). It has been used in many diseases including stroke and is the only fatigue measure that has a cut-off score for stroke patients (≥24 indicating post-stroke fatigue) ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the consumption of skeletal muscle content will lead to a lack of energy and a feeling of general weakness, and the further fatigue reaction will directly reduce physical activity, good mental state, and physical recovery speed, forming an adverse cycle of reduced ADL and increasing risk of stroke recurrence. [25] A survey of the elderly in Chinese communities [26] also showed that sarcopenia accounted for a considerable proportion (25%) in the elderly cohort and was independently associated with disability and poor ADL. Chen et al [27] found in the hip fracture cohort that sarcopenia significantly reduced ADL in patients with hip fracture, especially men.…”
Section: Discussionmentioning
confidence: 99%